Cross‐Sectional Association of State Recess Laws With District‐Level Policy and School Recess Provision in the United States. (13th April 2022) - Clevenger, Kimberly A.; Lowry, Mark; Perna, Frank M.; Berrigan, David
ABSTRACT: BACKGROUND: State recess laws are recommended to encourage adequate and equitable access to recess and its benefits, but the downstream effects of state recess laws are unknown. We examined the association of state recess laws with district‐level policy and school recess provision. METHODS: This is cross‐sectional analysis of the School Health Policies and Practices Survey, a US nationally representative sample of school districts (2016) and schools (2014). State‐level recess laws were coded as none, recommend, or require recess. Logistic and linear regression were used to examine the association between state law with district policies and school recess provision, respectively. Data from 2000 are presented to highlight changes in recess policy and provision over time. RESULTS: The odds of a district policy requiring recess were 2.22 and 2.34 times greater when state recess law recommended or required recess, respectively, compared to states with no recess policy. There were no significant differences in school‐level recess provision by state recess law but point estimates from 2000 indicated states without a law had the largest declines in recess provision over time. CONCLUSIONS: State recess laws are positively associated with district‐level policy. Effects at the school level are unclear and continued surveillance is needed.